2005
DOI: 10.1007/s00436-005-1323-9
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin overcomes the inhibitory effect of nitric oxide on Leishmania

Abstract: Upon Leishmania infection, macrophages are activated to produce nitrogen and oxygen radicals simultaneously. It is well established that the infected host cells rely on nitric oxide (NO) as the major weapon against the intracellular parasite. In India where leishmaniasis is endemic, the spice turmeric is used prolifically in food and for insect bites. Curcumin, the active principle of turmeric, is a scavenger of NO. This report shows that curcumin protects promastigotes and amastigotes of the visceral species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 47 publications
(46 reference statements)
1
29
0
1
Order By: Relevance
“…Anti-protozoal activities of Cur have also been documented in in vitro studies against Leishmania major promastigotes by Rasmussen et al (2001) and amastigote-like cells of L. major by Saleheen et al (2002). Similar studies were done by Araujo et al (1999) and Chan et al (2005) to show the in vivo effects of Cur on Leishmania and Plasmodium in animal models.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Anti-protozoal activities of Cur have also been documented in in vitro studies against Leishmania major promastigotes by Rasmussen et al (2001) and amastigote-like cells of L. major by Saleheen et al (2002). Similar studies were done by Araujo et al (1999) and Chan et al (2005) to show the in vivo effects of Cur on Leishmania and Plasmodium in animal models.…”
Section: Discussionmentioning
confidence: 53%
“…However, Cur in the present study was the least effective one against Giardia trophozoites. Chan et al (2005) related the weak effect of Cur in parasitic infection to its anti-oxidant and antiinflammatory activities, which may lead to exacerbation of the infection, as one of the most important defense mechanisms in controlling parasitic infections in the generation of reactive oxygen species and inflammation. Aditya et al (2010) overcame the poor bioavailability and the chemical instability of Cur by studying a novel approach for the Intestine 8…”
Section: Discussionmentioning
confidence: 99%
“…One of the most potent veterinary anticoccidials, toltrazuril, is believed to achieve some, if not all, of its beneficial effect by limiting the degree of lipid peroxidation [48]. Plants of the genus Curcuma, including C. longa (turmeric), has anti-oxidant and anti-inflammatory properties which could be detrimental for disease outcome and Curcumin is thought to be used to eliminate the intracellular parasites [49], [50], [51], [52]. Moreover, Allen and Danforth [53] concluded that feed supplementations with products that have antioxidant properties such as the spice tumeric (1%), as well as its main medicinal component, curcumin (0.05%) appear effective in reducing upper-and midsmall-intestinal infections caused by E. acervulina and E. maxima.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite its in vitro parasiticidal activity, there was concern that curcumin's antioxidant and ROS-scavenging ability may overcome the in vivo inhibitory effects of macrophage-produced nitric oxide on protozoan parasites (7). Since nitric oxide has a crucial role in eliminating infections such as malaria parasites (3,14), the ROS-scavenging activity of curcumin may exacerbate parasitic infections.…”
Section: Discussionmentioning
confidence: 99%